Cathepsin S activation contributes to elevated CX3CL1 (fractalkine) levels in tears of a Sjögren’s syndrome murine model - Fu, Runzhong (Sci Rep, 2020)
Autoimmune dacryoadenitis and altered lacrimal gland (LG) secretion are features of Sjögren’s syndrome (SS). Activity of cathepsin S (CTSS), a cysteine protease, is significantly and specifically increased in SS patient tears. The soluble chemokine, CX3CL1 (fractalkine), is cleaved from membrane-bound CX3CL1 by proteases including CTSS. We show that CX3CL1 is significantly elevated by 2.5-fold in tears (p = 0.0116) and 1.4-fold in LG acinar cells (LGAC)(p = 0.0026) from male NOD mice, a model of autoimmune dacryoadenitis in SS, relative to BALB/c controls. Primary mouse LGAC and human corneal epithelial cells (HCE-T cells) exposed to interferon-gamma, a cytokine elevated in SS, showed up to 9.6-fold (p ≤ 0.0001) and 25-fold (p ≤ 0.0001) increases in CX3CL1 gene expression, and 1.9-fold (p = 0.0005) and 196-fold (p ≤ 0.0001) increases in CX3CL1 protein expression, respectively. Moreover, exposure of HCE-T cells to recombinant human CTSS at activity equivalent to that in SS patient tears increased cellular CX3CL1 gene and protein expression by 2.8-fold (p = 0.0021) and 5.1-fold (p ≤ 0.0001), while increasing CX3CL1 in culture medium by 5.8-fold (p ≤ 0.0001). Flow cytometry demonstrated a 4.5-fold increase in CX3CR1-expressing immune cells (p ≤ 0.0001), including increased T-cells and macrophages, in LG from NOD mice relative to BALB/c. CTSS-mediated induction/cleavage of CX3CL1 may contribute to ocular surface and LG inflammation in SS.